FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMBELIAN BUAH IMPOR DI PASAR MODERN KOTA PANGKALPINANG - Fadila, Fanny; Karsiningsih, Eni; Bahtera, Novyandra Ilham (Fakultas Pertanian, Universitas Janabadra, 2024)
The objectives of this research are to determine the influence of price, fruit quality, shop atmosphere, service quality and location on the decision to purchase imported fruit in the modern market of PangkalpinangCity . The time and place of this research was carried out from July 2023 to September 2023 in the modern markets of Pangkalpinang City, namely Transmart and Grand Puncak Lestari. The research method used was purposive sampling with a sample size of 100 respondents. Data analysis uses SEM-PLS (Structural Equation Modeling-Partial Least Square) analysis. The research results show that price, shop atmosphere and location have a direct influence on the decision to purchase imported fruit in the modern market of Pangkalpinang City. Meanwhile, fruit quality and service quality do not influence the decision to purchase imported fruit in the modern market in Pangkalpinang City.